Using related Legal Systems to secure the Execution of just Satisfaction awarded by the ECtHR - Achilleas Demetriades; Alexandros Demetriades (LeXonomica, 2021)
The present article hopes to initiate a discussion concerning alternative methods through which applicants themselves can ensure that recalcitrant respondent States comply with their obligations to execute the judgments of the ECtHR. This may be done by mobilising related legal systems towards this end. This paper focuses on the 'just satisfaction' element of the judgment and examines one possible avenue through which applicants themselves can secure their payment. The relevant course of action has two elements: (i) securing the recognition of the ECtHR's order to pay within the national legal order of a non-respondent High Contracting Party to the Convention and requesting that the relevant national court issue a third-party debt order against the European Commission and (ii) securing the waiver of the European Commission's immunity.Povzetek. Namen članka je začeti razpravo o alternativnih metodah, s katerimi lahko pritožniki sami zagotovijo, da nepopustljive države toženke izpolnijo svoje obveznosti izvršitve sodb ESČP. To je mogoče doseči z mobilizacijo sorodnih pravnih sistemov v ta namen. Ta članek se osredotoča na element "pravičnega zadoščenja" iz odločb ESČP in preučuje eno od možnih poti, s katerimi lahko prosilci sami zagotovijo plačilo. Ustrezna pot ravnanja ima dva elementa: (i) zagotovitev priznanja sklepa ESČP o plačilu v nacionalnem pravnem redu pogodbenice Konvencije, ki ni odgovorna, in zahteva, da zadevno nacionalno sodišče izda sklep o dolžniški obveznosti tretje osebe zoper Evropsko komisijo, ter (ii) zagotovitev odvzema imunitete Evropski komisiji.